B2, B7 or B10: Which palm-based blend mandate wise to be chosen in Malaysia? - Applanaidu, Shri Dewi; Zainal Abidin, Norhaslinda; Md Ali, Anizah (2015)
The diminishing fossil energy resources, coupled with heightened interest in the abatement of greenhouse gas emissions and concerns about energy security have motivated Malaysia to produce palm-based biodiesel and it has been started to be exported since 2006. In line with this issue, the government in Malaysia launched the palm-based biodiesel blending mandate of five percent (B5) in the federal administration of Putrajaya on 1st June 2011.This was then followed by four states: Malacca on July 11, Negeri Sembilan on August 1, Kuala Lumpur on September 1 and Selangor on October 1 of the same year but it is yet to be implemented nationwide. However what is the wise blend mandate to be chosen? Thus, this paper seeks to examine the possible impact of various blend mandates implementation (B2, B7 and B10) on the palm oil industry market variables (stock and price) since the main aim of biodiesel industry in Malaysia is to reduce domestic palm oil stock to below one million tones and provide a floor price to support Crude Palm Oil (CPO) prices at RM2,000 per tonne. A structural econometric model consisting of nine structural equations and three identities was proposed in this study. The model has been estimated by two stage least squares (2SLS) method using annual data for the period 1976-2013. The study indicates that counterfactual simulation of a decrease from B5 to B2 predicts a decrease (11.2 per cent) in CPO domestic consumption for biodiesel usage, 731.02 per cent reduction in CPO stock and an increase of 27.41 percent in domestic price of CPO. However the increase in the blend mandate from B5 to B7 and B10 suggest that domestic consumption of CPO for biodiesel purpose increase 7.40 and 18.55 percent respectively. The interesting findings in this study suggest that no matter whether Malaysian government increase or decrease the blend mandate the increase in the price of CPO are the same with an increase of is 27.41 percent. Hence, this study suggests that the lower blend mandate is the most favourable on.+-e compared to increasing it in this short period due to high production cost of CPO prices.However, future study on economic feasibility of palm-based biodiesel has to be conducted to support this study.